Investigating a self-reference effect in musical aesthetics. (24th April 2020) - Grassi, Massimo; Kasdan, Anna; Belfi, Amy M.
Abstract: Previous work on aesthetic experience suggests that aesthetic judgments are self-referential. The self-reference effect (SRE) is the tendency for individuals to show improved memory for items that are judged in relation to themselves. The current study sought to understand if the SRE exists for aesthetic judgments of music. Participants heard musical excerpts (classical, jazz, and electronic) and rated either a) how much they liked the music (Self condition), b) how much a close relative or friend would like the music (Other condition), or c) the genre of the music (Genre condition). After a retention interval, participants completed a recognition memory task for the musical excerpts. Participants did not show improved memory for musical excerpts encoded in the Self condition. These results extend the concept of the SRE into the domain of aesthetic judgments, but do not provide support for a memory advantage when making aesthetic judgments in relation to the self.